Modeling heat and mass transfer during artificial ground freezing considering the influence of water seepage. (15th September 2022) - Hou, Shanshan; Yang, Yugui; Cai, Chengzheng; Chen, Yong; Li, Fulin; Lei, Dawei
Highlights: The dynamic liquid–ice equilibrium relationship considering the contribution of water seepage pressure is established. The relationship between the decrease of water freezing point temperature and water seepage pressure is derived. A thermal-hydraulic model is established for AGF under water seepage. The temperature field evolution characteristics in the subway cross passages freezing are analyzed. Abstract: In the system of artificial ground freezing under water seepage, the dynamic liquid–ice phase equilibrium relationship considering the contribution of water seepage pressure was established based on the classical thermodynamics fundamentals. The freezing characteristic function was represented by combining the Young–Laplace law with van Genuchten model. A thermal-hydraulic model of saturated porous media considering dynamic liquid–ice phase equilibrium was established and validated thorough laboratory tests under various seepage velocities. The temperature field evolution laws of sand, silty and clay grounds were studied based on the thermal-hydraulic model. The temperature field development laws of primary side tunnel of subway cross passages in silty-clay layer were analyzed by applying the thermal-hydraulic model. The relationship between water seepage pressure and the decrease of water freezing point temperature was obtained according to the dynamic liquid–ice phase equilibrium. Compared with the simulation results of considering static liquid–ice phase equilibrium relationship, considering the dynamic liquid–ice phase equilibrium relationship changes the distribution of water-ice phase transition front and has significant influence on the temperature evolution in silty ground. However, that influence in sand ground and clay ground is insignificant because of the relatively lower water seepage pressure in sand ground and poor thermal conductivity in clay ground. Due to the cold energy accumulation bring by water seepage, the freezing rate in the downstream of freezing pipes is faster than that in the upstream of freezing pipes. This effects are exacerbated by lower decrease of water freezing point temperature caused by minor water seepage pressure in the downstream of freezing pipes. Four representative temperature measured points were selected to acquire the relationship between simulation and on-site temperatures. It was observed that the trends of simulation results reflect the tunnel freezing process well.